Effect of Treated Wood on Biosolids Composting. Issue 3 (3rd July 2017) - Kamal, Abu; Wichuk, Kristine; McCartney, Daryl; Londry, Kathleen; Felske, Christian
ABSTRACT: The possibility of using construction and demolition (C&D) waste wood as a bulking material in biosolids composting was investigated. Potential contaminants in C&D waste wood include arsenic (As), chromium (Cr), and copper (Cu) from treated wood, and lead (Pb) from paints. Untreated and treated woodchips from C&D wood were mixed with biosolids, composted using an aerated static pile process, and cured. There were no significant differences between untreated and treated woodchips with respect to composting process, time to stability, or product quality. Composting parameters monitored included moisture content, pH, electrical conductivity, organic matter degradation, fecal coliform levels, and stability by respirometry. Finished compost quality was evaluated in terms of potential toxic elements (PTE) levels. PTE values in treated woodchips (26 ± 35, 29 ± 41, 56 ± 46, and 5 ± 5 µg·g −1 for As, Cr, Cu, and Pb, respectively) were higher and more variable than those in the untreated woodchips (3 ± 3, 17 ± 8, 13 ± 2, and 0.5 ± 0.0 µg·g −1 ). However, both untreated and treated wood compost products met Canadian Council of Ministers of the Environment Category B values for PTE. In addition, and only molybdenum (Mo) and Cu exceeded Category A thresholds. Biosolids were the most significant contributor of Mo, while Cu contributions came from both biosolids and wood chips; some samples of pressure-treated wood showed concentrations of Cu in the range of 765 to 8, 455 µg·g −1 . The results of this study suggest that treated wood from C&D recycling facilities will not significantly degrade the quality of biosolids compost products.